2018
DOI: 10.1002/ijc.31949
|View full text |Cite
|
Sign up to set email alerts
|

Nonaspirin NSAIDs and contralateral breast cancer risk

Abstract: Laboratory studies suggest that inhibition of the cyclooxygenase (COX)-2 enzymes inhibits breast cancer development. We aimed to evaluate whether postdiagnosis use of COX-2 selective or other nonaspirin nonsteroidal anti-inflammatory drugs (NSAIDs) reduce the risk of contralateral breast cancer (CBC) among Danish breast cancer patients. From the clinical database of the Danish Breast Cancer Group, we identified 52,723 women diagnosed with breast cancer between 1996 and 2012. Data on nonaspirin NSAID use, CBC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…With the advent of aspirin in the 1990s, the application of NSAIDs has been extended to the treatment of pain, fever, and other inflammatory processes. Multiple studies have addressed the preventative effect of NSAIDs on cancer, leading to reduced incidence of colorectal [277], breast [278], and esophageal cancer [279]. In a randomized clinical trial, daily administration of aspirin effectively prevented adenoma growth in patients with familial adenomatous polyposis [280,281].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…With the advent of aspirin in the 1990s, the application of NSAIDs has been extended to the treatment of pain, fever, and other inflammatory processes. Multiple studies have addressed the preventative effect of NSAIDs on cancer, leading to reduced incidence of colorectal [277], breast [278], and esophageal cancer [279]. In a randomized clinical trial, daily administration of aspirin effectively prevented adenoma growth in patients with familial adenomatous polyposis [280,281].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…The effect of aspirin and other NSAID use on CBC risk has been studied in two Danish cohort studies (Table 3 and Figure 1). Among 52,723 breast cancer patients, HRs for CBC of 0.91 (95% CI: 0.76-1.09) and 0.98 (95% CI: 0.87-1.11) were observed for low-dose aspirin (75-150 mg) and non-aspirin NSAID use, respectively [65,66]. The ongoing Add-Aspirin trial (NCT02804815), assessing the efficacy of adjuvant aspirin (100 mg or 300 mg versus placebo) in breast cancer patients, may provide further understanding of the potential of aspirin in prevention of CBC among breast cancer survivors.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…It has been reported that people who regularly take aspirin or other non-steroidal anti-inflammatory drugs have a lower risk of colon cancer, gastric cancer, esophageal cancer, lung cancer and breast malignancy [4][5][6][7]. Non-steroidal anti-inflammatory medications suppress the synthesis of prostaglandin and block prostaglandin-induced immunosuppression to enhance immune responses and induce cell apoptosis [8]. The purpose of this study was to explore the influences of aspirin on the proliferation and apoptosis of gastric cancer cells through the interleukin (IL)-6/signal transducer and activator of transcription 3 (STAT3) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%